Momentum And Investor Sentiment: Evidence From Asian Stock Markets - Anusakumar, Shangkari V. (2013)
Momentum is a well-known stock market anomaly that has yet to be fully explained. Though momentum has been widely examined in the US and other markets, literature on Asian stock markets is sparse. Moreover, effect of sentiment on momentum has not been investigated in non US markets. This study hopes to fill the identified gaps. Notably, this study is the first to propose and investigate the influence of global and holding period sentiments on momentum. This thesis firstly explores the presence of momentum in 13 Asian countries (Bangladesh, China, Hong Kong, India, Indonesia, Japan, Malaysia, Pakistan, Philippines, Singapore, South Korea, Taiwan and Thailand) using data from January 2000 to December 2011. Secondly, effect of firm size and trading volume on momentum are tested. Finally, the pivotal part of the thesis is the analysis of the effect of sentiment on momentum. Specifically, the effects of local, global and holding period sentiments are investigated. On average, momentum is found to be present in Asia. On an individual country basis, momentum portfolio returns are predominantly positive and statistically significant for approximately one third of the countries. Segregation of the sample by size, volume and sentiment further showed increases in momentum. Taking into consideration sentiment and firm size yields the most promising results wherein all but one country had momentum. The findings reveal that sentiment plays a crucial role in the manifestation of momentum.